Analgesic effects and arthritic changes following tramadol administration in a rat hip osteoarthritis model. Issue 8 (15th November 2021) - Kanno, Keijiro; Suzuki‐Narita, Miyako; Kawarai, Yuya; Hagiwara, Shigeo; Yoh, Satoshi; Nakamura, Junichi; Orita, Sumihisa; Inage, Kazuhide; Suzuki, Takane; Ohtori, Seiji
Abstract: We investigated the analgesic effects of tramadol and the arthritic changes following tramadol administration in the rat hip osteoarthritis (OA) model using mono‐iodoacetate (MIA). The right hip joints of male Sprague–Dawley rats ( n  = 5 rats/group) in the Sham group were injected with 25 μl of sterile saline and 1% of fluorogold (FG) retrograde neurotracer. In the MIA + Vehicle and MIA + Tramadol groups, FG and 25 μl of sterile saline with 0.5 mg of MIA were injected into the right hip joint. The MIA + Vehicle and MIA + Tramadol groups were administered daily for 4 weeks, either sterile saline (10 mg/kg, intraperitoneal [i.p.]) or tramadol (10 mg/kg, i.p.). We assessed hyperalgesia every week after MIA administration. Histopathological changes and immunoreactive neurons for calcitonin gene‐related peptide (CGRP) in dorsal root ganglia (DRG) were evaluated after 4 weeks of treatment. MIA injection into the hip joint led to mechanical hyperalgesia ( p  < 0.01), which was significantly reduced by tramadol administration ( p  < 0.01). Furthermore, daily i.p injection of tramadol significantly suppressed CGRP expression in DRG ( p  < 0.0001). MIA + Vehicle and MIA + Tramadol groups showed significant cartilage reduction and degeneration compared to the Sham group ( p  < 0.0001). Interestingly, OA changes significantly progressed in the MIA + Tramadol group compared to the MIA + Vehicle group ( p  < 0.0001).